2007
DOI: 10.1007/s11064-007-9464-0
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethioninemia Increases Cerebral Acetylcholinesterase Activity and Impairs Memory in Rats

Abstract: In the present study we investigated the effect of chronic hypermethioninemia on rat performance in the Morris water maze task, as well as on acetylcholinesterase (AChE) activity in rat cerebral cortex. For chronic treatment, rats received subcutaneous injections of methionine (1.34-2.68 micromol/g of body weight), twice a day, from the 6th to the 28th day of age; control rats received the same volume of saline solution. Groups of rats were killed 3 h, 12 h or 30 days after the last injection of methionine to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 34 publications
1
16
0
1
Order By: Relevance
“…The L-methioninetreated rats are mostly used for the assessment of HHcy and its secondary complications, including ED and VaD (Koladiya et al 2008;Sain et al 2011). HHcy has been reported to produce cognitive dysfunction (Streck et al 2004;Baydas et al 2005) and increase in the brain AChE activity (Stefanello et al 2007). HHcy has been reported to induce endothelial dysfunction by decreasing the bioavailability of NO and by increasing vascular oxidative stress (Abahji et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The L-methioninetreated rats are mostly used for the assessment of HHcy and its secondary complications, including ED and VaD (Koladiya et al 2008;Sain et al 2011). HHcy has been reported to produce cognitive dysfunction (Streck et al 2004;Baydas et al 2005) and increase in the brain AChE activity (Stefanello et al 2007). HHcy has been reported to induce endothelial dysfunction by decreasing the bioavailability of NO and by increasing vascular oxidative stress (Abahji et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Equally, the clock output genes we studied have been implicated in neurological disturbance. Ahcy encodes S-adenosylhomocysteine hydrolase, defects of which cause hypermethioninemia (Baric et al, 2004), and cognitive deficits in rats (Stefanello et al, 2007). Notably, HD patients are reported to have abnormal handling of homocysteine (Andrich et al, 2004), and mutant huntingtin influences homocysteine metabolism by modulating the activity of cystathionine-␤-synthase (Boutell et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that chronic L-methionine treatment and experimental Hhcy produce cognitive dysfunction 23,24) and increase in brain AChE activity. 25) L-methionine-induced Hhcy is a well established model of experimental endothelial dysfunction. 10) Hhcy has been reported to induce endothelial dysfunction by decreasing the bioavailability of NO and by increasing vascular oxidative stress.…”
Section: Discussionmentioning
confidence: 99%